Renal Denervation in Isolated Systolic Hypertension Using Different Catheter Techniques and Technologies: Insights From a Randomized Trial. Issue 2 (August 2019) - Fengler, Karl; Rommel, Karl-Philipp; Lapusca, Razvan; Blazek, Stephan; Besler, Christian; Hartung, Philipp; von Roeder, Maximilian; Kresoja, Karl-Patrik; Desch, Steffen; Thiele, Holger; Lurz, Philipp
Abstract : Patients with isolated systolic hypertension (ISH) are thought to show a diminished blood pressure (BP)–lowering effect after renal sympathetic denervation (RDN). This conclusion is mostly derived from unipolar radiofrequency catheter ablation studies. Limited data for newer RDN technologies exist. We used data from the RADIOSOUND-HTN (Three-Arm Randomized Trial of Different Renal Denervation Devices and Techniques in Patients With Resistant Hypertension) comparing 3 different RDN approaches to investigate a possible interaction between ISH and RDN response. One hundred twenty patients were stratified by having ISH or combined systolic-diastolic hypertension (CH). Of these, 39 underwent radiofrequency ablation of the renal main arteries, 39 combined radiofrequency ablation of the main and branch arteries, and 42 were treated with ultrasound-based ablation of the main renal artery. Patients with ISH (n=61) were older and had lower systolic and diastolic BP on ambulatory measurement (ambulatory BP measurement) at baseline in comparison to CH (n=59). At 3 months, patients with ISH showed a less pronounced BP-lowering effect of RDN as compared to patients with CH (daytime average −5.9±11.8 versus −13.3±11.7 mm Hg, P =0.001). This difference was significant for radiofrequency ablation of the renal main arteries and ultrasound-based ablation of the main renal artery treatment but did not reach significance in the radiofrequency ablation of the main and branch arteries group. After adjustment for baseline BP values and age, there was no significant difference in BP reduction between ISH and CH. Using unadjusted BP values, RDN seems to be more effective in CH than in ISH. However, adjusting for baseline BP values revealed similar BP reduction in ISH and CH patients, irrespective of the RDN treatment used. The value of ISH as predictor for successful RDN might have been overestimated in the past. Clinical Trial Registration—: URL: http://www.clinicaltrials.gov . Unique identifier: NCT02920034.